Preliminary study of the effect of ultrasound on physicochemical properties of red wine. Issue 1 (2nd January 2016) - Zhang, Qing-An; Shen, Yuan; Fan, Xue-Hui; García Martín, Juan Francisco
Abstract : Ultrasound is regarded as a potential alternative method for improving the quality of some wines. This study was initiated with the objective of evaluating the effects of ultrasound on some important physicochemical properties of red wine such as chromatic characteristics (CC), electrical conductivity (EC), pH, titratable acidity (TA), total phenolic compounds (TPCs) and DPPH (1, 1-diphenyl-2-picryl-hydrazyl) free radical scavenging activity (DFRSA). The operational parameters assessed were ultrasound power, ultrasound frequency, exposure time and bath temperature. Results illustrated that there were significant changes in CC, EC and TPC while pH and TA hardly changed except for samples treated at high temperatures. DFRSA was correlated to TPC during ultrasonic treatment. Application of principal component analysis to the experimental data suggested that exposure time was the factor with the greatest ability to induce changes on wine. Results suggested that ultrasound may be applied to improve some physicochemical properties of red wine.